Professor of matematics Aurel Edmund Voss and University of Lithuania - Puišo, Judita; Larionovienė, Dalia (Lietuvos matematikos rinkinys, 2019)
Professor Aurel Edmund Voss was a German mathematician, best known for his contributions to application of geometry in natural science and mechanics. The collection of books of professor A.E. Voss was bought and used by Faculty of Matematics and Nature of Univerity of Lithuania. In 1940’s the collection of books of prof. A.E. Voss was transfered to Vilnius University. The aim of the work was to investigate collections of books of libraries of Lithuania and to present books of prof. A.E Voss to scientiﬁc society of Lithuania.
Keywords: matematics; collection of books; University of Lithuania; Vilnius University